Coherent multiphoton photoemission spectroscopy of image-potential state on Ir(111) surface - Yu-Chan Tai; Chih-Wei Luo; Noriaki Takagi; Hiroshi Ishida; Chun-Liang Lin; Ryuichi Arafune (Applied Physics Express)
Multiphoton photoemission provides a means to investigate unoccupied electronic states via nonlinear light-matter interactions. In this work, we employ five-photon photoemission spectroscopy to identify, for the first time, the image-potential state (IPS) on the Ir(111) surface. Distinct from commonly studied noble metals such as Cu and Ag, the Ir(111) electronic structure leads to a strong sensitivity to excitation energy: a reduction from 1.57 eV to 1.49 eV significantly diminishes the signal. The theoretical analysis attributes this effect to the d -band proximity to the Fermi level, which influences the initial-state population and transition probabilities governing the multiphoton excitation pathways.